Komposisi Sampah Dan Kualitas Air Lindi Tempat Pemrosesan Akhir Winongo - Pratama Restu Aji; Raden Kokoh H (Jurnal Serambi Engineering, 2024)
Waste generation and management is an important aspect of human life, with various types of waste being generated on a daily basis. In Madiun City, waste is managed from source to disposal at the Winongo landfill. However, the landfill faces challenges due to the high daily waste production of over 100 tonnes of both organic and inorganic waste. This high waste production causes problems such as leachate pollution, where the quality of the waste greatly affects the quality of the leachate. This study focuses on the effect of waste composition on the quality of leachate at the Winongo Landfill in Madiun City, using primary data from the East Java Environmental Agency in 2023. Laboratory results show that leachate parameters such as COD, BOD, TSS, pH and total N exceed regulatory standards due to the dominance of organic waste in the landfill. Therefore, treatment methods using pond systems are recommended in order to meet acceptable discharge standards and protect the environment. This research highlights the importance of understanding the relationship between waste composition and leachate quality for effective waste management and environmental protection.